Peculiarities of formation and calculation of maximum runoff for Terisbutak river (Journal of Geography and Environmental Management, 2018)
There have been figured out the main peculiarities of water regimes and tendencies in maximumwater runoff formation within small mountain rivers that are not supplied with glacial sustention in conditionsof the northern slope of Ile Alatau. The work has been accomplished on the example of Terisbutak River, which is a typical representation of small rivers in the researched area. There have been analysesthe materials of long-term observations over maximum water consumption and spring inundation runoff.There have been defined the quantitative characteristics of maximum urgent and average daily waterduties, volumes of runoff in the period of inundation, and calculation hydrographs of inundation havebeen obtained. The reasons of mud stream uprising have been researched, and also there have been calculatedthe maximum duties and density of mudflow mass for water-sedimentary and mud-stone streamsthat have the possibility to origin within Terisbutak river.